2000
DOI: 10.1046/j.1365-2265.2000.00909.x
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of vitamin D receptor gene polymorphisms for growth inhibition of cultured human peripheral blood mononuclear cells by 1,25‐dihydroxyvitamin D3

Abstract: The present study demonstrates for the first time in cells with a natural VDR genotype a direct functional consequence of the VDR gene translational start-site polymorphism for the action of 1,25-(OH)2D3. Especially under conditions of vitamin D insufficiency these findings might have clinical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
117
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(123 citation statements)
references
References 29 publications
4
117
1
1
Order By: Relevance
“…In the two studies involving NSCLC patients, there was no association between Cdx-2, Fok1, or Bsm1 VDR polymorphism and RFS or survival in one of them, involving patients with early-stage disease [29], whereas in the second study [17], the Fok1 genotype T was associated with a poor prognosis. The HR for death was 1.32 (95% CI, 0.98 -1.77) for C/T and 1.41 (95% CI, 0.96 -2.07) for T/T (p for trend ϭ .04), compared with the C/C reference group in patients with advanced or metastatic NSCLC.…”
Section: Vdr Expression and Relevant Polymorphismsmentioning
confidence: 91%
See 1 more Smart Citation
“…In the two studies involving NSCLC patients, there was no association between Cdx-2, Fok1, or Bsm1 VDR polymorphism and RFS or survival in one of them, involving patients with early-stage disease [29], whereas in the second study [17], the Fok1 genotype T was associated with a poor prognosis. The HR for death was 1.32 (95% CI, 0.98 -1.77) for C/T and 1.41 (95% CI, 0.96 -2.07) for T/T (p for trend ϭ .04), compared with the C/C reference group in patients with advanced or metastatic NSCLC.…”
Section: Vdr Expression and Relevant Polymorphismsmentioning
confidence: 91%
“…VDR polymorphisms comprise a cluster of tightly linked polymorphisms at the 30-end (Apa1, Bsm1, Taq1, and a length polymorphism of a polyadenyl microsatellite in the 30-untranslated region) and the 50-end of the gene (Fok1 and Cdx-2) [17,18].…”
Section: Vdr Expression and Relevant Polymorphismsmentioning
confidence: 99%
“…Arai et al (1997) showed that compared with the FokI T/T genotype, FokI C/C had 1.7-fold greater function of vitamin D-dependent transcriptional activation of a reporter construct under the control of a vitamin D response element in transfected HeLa cells. Similarly, Colin et al (2000) showed a significantly lower (50%) effective dose of 1,25-(OH) 2 D 3 in the FokI C/C genotype than in FokI C/T genotype. By switching from ATG (FokI T) to ACG (FokI C) polymorphism, the first potential start site moves to the 3 0 direction, resulting in proteins that are three amino acids shorter and more functional (Gross et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…55 The effect on ED 50 and not on maximal inhibition was regarded as potentially significant because in this way the effect of a polymorphism would depend on the 1,25-dihydroxyvitamin D 3 status of the carrier. In summary, the functional effects of the VDR polymorphism so far reported cannot explain how the VDR contributes to the pathogenesis of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%